Structural imbalance in youth weight management policies in China: a three-dimensional analysis of school responsibility and collaborative support - Yun Zhang; Xiangyu Wang (Frontiers in Public Health, 2026)
Objective Youth weight management is a complex public health challenge requiring coordinated action across settings, with schools serving as primary implementation environments. This study examined how Chinese national policies allocate school responsibilities and configure external collaborative support. Methods Thirty-six national policy documents issued in China between 2016 and 2025 were systematically analyzed. Unlike one-dimensional frequency analyses, the proposed framework linked policy targets, instruments, and implementing actors through three cross-dimensional co-occurrence matrices. NVivo-assisted coding, descriptive association indicators, and a sensitivity analysis were used to characterize policy-design patterns. Results Environmental targets, capacity-building instruments, and schools were the most frequent categories. In the policy corpus, schools were overrepresented in pairings with command instruments and physical fitness targets, whereas external actors appeared in differentiated but weakly integrated pairings dominated by exhortation and capacity-building tools. Incentive and system-change instruments were comparatively uncommon. These textual patterns indicate that national policy design concentrates specified obligations in schools while providing relatively fewer structural and incentive mechanisms to connect schools with external actors. Conclusion The three-dimensional framework identifies a school-centered policy design in which mandated tasks are more prominent than explicit mechanisms for systemic empowerment and cross-sector coordination. Policymakers can use the framework to compare assigned tasks with enabling instruments, clarify responsibility boundaries, establish school–health referral and coordination protocols, and match school mandates with earmarked resources. Because the analysis is limited to policy texts, the findings describe policy design rather than verified implementation or effectiveness.